Çocuklar için felsefe eğitim programının altı yaş grubu çocuklarının, atılganlık, işbirliği ve kendini kontrol sosyal becerileri üzerindeki etkisi - Okur, Melek (My University, 2008)
IV ABSTRACT EFFECTS OF PHILOSOPHY FOR CHILDREN ON SOCIAL SKILLS THAT ARE: ASSERTIVENESS, SELF-CONTROL AND COOPERATION AT CHILDREN OF SIX YEARS OLD. Melek OKUR- stanbul 2008 The aim of this reaseach is analysing P4C (Philosophy for children) as a pedogogical program which is focused on the improvement of children’s specific social skills that are: assertiveness, self-control, and cooperation. Our primary concern was to introduce P4C in terms of pedogogical systematic applications. The reseach was carried out stanbul, district of Uskudar at IMKB Vocational School’s Kindergarten. The participants were 24 of 6 year-old children during 2007- 2008 academic year. Children were divided into two groups to form one experiment group, and one control group of equal number. The boys and girls were equal numbers in the groups too. The educational programme was developed to evaluate the effects of method of philosophy for children on children’s assertiveness, self control and cooperation skills, based on Matthew Lipman’s. The educational process consisted of ten 40 minute sessions for 8 weeks. Both sessions for experiment and control groups included story-telling and drama and for experiment group the programme also included discussions initiated by teacher’s questions which aimed the inquiry of philosophical concepts. A Social Skill Rating scale; Teacher Form (Kamaraj, 2004) were administered to experiment, control groups as a pre-test and post test. For the statistic analysis, the T-test and test of Mann Whitney-U were applied. According to the findings of my empirical work, there was significant improvement in children cooperative skills, self control and assertiveness. V The results indicate that children at the age of 6, showed a meaningful difference statistically at their social skill level in Philosophy for Children education Programme performances. At the end of the research; we can see that Philosophy for Children affects 6 year age children’s social skills that are: assertiveness, self-control, and cooperation. There is not any difference found related to gender of children. Key words: Philosophy For Children, Social Skill, Assertiveness, Self-control, Cooperation.
Keywords: Atılganlık, Çocuklarda; Eğitim; Felsefe_Öğrenim ve Öğretim; Sosyal Beceri, Çocuklarda